ADOPTED FOREIGNERS INHERITANCE BY INDONESIAN CITIZEN - Ong Argo Victoria; Muhammet Ebuzer Ersoy (Program Studi Magister (S2) Kenotariatan, Fakultas Hukum, Universitas Islam SUltan Agung, 2020)
Adoption is a legal act which distract a child from the environment of its parents, legal guardian, or other person responsible for the care, education and parenting, into a family environment with foster parents. It lawful both adoptions between Indonesian citizens and adoption among Indonesian citizens and foreigners. However, what legal consequences arising from the removal of the child? Is the adopted child could inherit from their foster parents or not? Or is there a way to pass down inheritance to adopted child who allowed the legislation? Therefore, this article will discuss,